2008
DOI: 10.1097/hjr.0b013e32830c1cc5
|View full text |Cite
|
Sign up to set email alerts
|

Does diagnosis of metabolic syndrome predict the likelihood of peripheral arterial disease as defined by a low ankle-brachial index?

Abstract: Screening of participants with MS does not improve the identification of abnormal ABI provided by diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…However and similar to the study by López-Suárez et al [9], when additionally adjusted by the presence of hyperglycemia (FPG a The multivariate adjusted model is adjusted for the age, LDL-C and the components of metabolic syndrome (FPG, HDL-C, TG, WC and the presence of hypertension). above 100 mg/dL), the inverse association between MetS and ABI lost statistical significance.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However and similar to the study by López-Suárez et al [9], when additionally adjusted by the presence of hyperglycemia (FPG a The multivariate adjusted model is adjusted for the age, LDL-C and the components of metabolic syndrome (FPG, HDL-C, TG, WC and the presence of hypertension). above 100 mg/dL), the inverse association between MetS and ABI lost statistical significance.…”
Section: Discussionmentioning
confidence: 87%
“…In line with this suggestion, the present study demonstrated that individual components of MetS including, elevated blood pressure and raised FPG are independently associated with lower readings of ABI and a significant association between lower ABI and MetS as a single entity was observed. However, additional screening of the MetS status may not improve the detection of asymptomatic PAD beyond the risk imposed by hyperglycemia and diabetes [9].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies found an association of PAD with MS according to the WHO criteria [19,20] unlike the study by Wong et al [21]. Concerning the association of PAD with MS according to NCEP-ATPIII, several studies found an association and others did not [19,22-24]. The study by Larsson et al goes in the direction of ours, especially since it is cohort study [19].…”
Section: Discussionmentioning
confidence: 61%
“…The study by Larsson et al goes in the direction of ours, especially since it is cohort study [19]. The risk of having PAD in another study was higher with the five elements of the MS combined [22], a study in Spain showed a 14 times higher risk of having a PAD in the presence of MS [23]. On the criteria of the AHA / NHLBI, one study found no association with PAD [25].…”
Section: Discussionmentioning
confidence: 91%